Polymer-Based Hydrogel Loaded with Honey in Drug Delivery System for Wound Healing Applications - Siti Nor Najihah Yasin; Zulfahmi Said; Nadia Halib; Zulaiha A Rahman; Noor Izzati Mokhzani (MDPI AG, 2024)
Indexed by WOS/Scopus/ERA